(3-Aminopropyl) triethoxysilane-functionalized silica nanocapsule adsorbent: Synthesis and analysis of physicochemical characteristics - Thangarajoo, N. (Academic Press Inc., 2022)
3-aminopropyltriethoxysilane (APTES)-functionalized silica nanocapsule (A-SiNC) was prepared from a one-step synthesis process for the application of post-combustion carbon dioxide (CO2) capture. A-SiNC was synthesized from the microemulsion method by using cetyl trimethylammonium bromide (CTAB) as a cationic surfactant, toluene as co-solvent, APTES as an amine group, and tetraethyl orthosilicate (TEOS) as silica base. The synthesis and functionalization were carried out in a variation of APTES using Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), nitrogen adsorption-desorption measurements (BET), and transmission electron microscopy (TEM). The results showed that silica nanocapsules (SiNC) potential to react until a temperature of 166 âÂ°C, which indicates a stable thermal decomposition property. The surface area and surface morphology were influenced by the presence of an amino group as APTES loaded SiNC provides a different mechanism compared to blank SiNC. The close-packed structure was seen and proven in A-SiNC based on the observation from TEM. Â© 2022 Elsevier Inc.